Violencia en la relación de noviazgo y estrés en estudiantes de la Universidad Nacional de Loja, periodo 2022-2023 - Ayala Armijos, Mercedes Fernanda (2024)
Dating violence is a problem faced by society and has harmful repercussions that range from the personal to the family environment, affecting physical, sexual and psychological health. The general objective of this research was to associate dating violence and stress in students of the Universidad Nacional de Loja. It corresponds to a study with a quantitative approach, non-experimental design, correlational and cross-sectional scope. Forty-seven nursing students participated, using the following instruments: DVQ-VP dating violence and victimization and perceived stress scale. The data were processed in SPSS 2.2 and analyzed through descriptive statistics with the nonparametric Tau Kendall B test. The results showed that 72.3% were between 18 and 22 years of age, 62.1% were women, most of the participants belonged to the third cycle, and 78.6% lived in the urban area. With respect to dating violence, the most significant percentage (51.1%) is found in the item "to keep her from leaving", of the coercion dimension on the scale "sometimes" and in a lower percentage, in the same dimension (2.1%), is located in the item "to put love to the test", on the scale "almost always". In terms of perpetration, the highest percentage (48.9%) is found in the item "compliant with study, but late for partner appointments", in the detachment dimension, scale "sometimes", and the lowest (2.1%) is found in the same dimension, item "not recognizing responsibility as a partner", scale "usually". Finally, with respect to perceived stress, 80.9% of the participants presented moderate stress. In conclusion, there is a significant relationship between violence from the dynamics of perpetration and the level of perceived stress; however, from the perspective of victimization, no significant relationship was found